3D layer-to-layer orthogonal interlock woven composites under monotonic loading: Multiscale modeling. (September 2017) - Muthukumar, M; Prasath, J; Sathish, S; Ravikumar, G; Desai, YM; Naik, NK
Multiscale modeling of 3D layer-to-layer orthogonal interlock woven composite structure for elastic and strength behavior is presented. Due to the inherent nature of weaving, 3D woven composites can be represented by repetitive unit cells at the meso level. The present study focuses on identifying different types of repetitive unit cells considering both the geometry and the boundary conditions. For a typical 3D layer-to-layer orthogonal interlock woven composite, there are eight types of meso repetitive unit cells taking into account both the geometry and the boundary conditions. Additionally, for a practical situation, fiber volume fraction (Vf ) in the impregnated strand is not uniform throughout the cross-section. In other words, Vf would be different for different micro repetitive unit cells. The properties of the macro structure, i.e. the 3D woven composite structure has been determined by applying periodic boundary conditions at micro and meso levels and iso-strain conditions at the macro level using finite element analysis. The continuity between the blocks is provided by merging the nodes in the intersection regions. The effect of different Vf at different locations in the transverse cross-section of the strand on the elastic and the strength properties of 3D layer-to-layer woven composite structure is presented.